Gluthathione S-transferase-resuscitation-promoting factor B recombinant protein of Mycobacterium tuberculosis induces the production of interferon-γ and interleukin-12 in mice splenocytes (Medical Journal of Indonesia, 2019)
BACKGROUND As the only TB vaccine available, Bacillus Calmette-Guérin shows variable efficacy in adults and does not provide protection against the resuscitation of latent TB infections. Resuscitation-promoting factor B (RpfB) is a protein produced by Mycobacterium tuberculosis during the resuscitation phase and is promising as a novel TB vaccine. This study was aimed to analyze the immunogenicity of the gluthathione S-transferase (GST)-RpfB recombinant protein on mice splenocytes in vitro. METHODS After induction with isopropyl β-D-1-thiogalactopyranoside, the protein was extracted by sonication followed by solubilization in 8 M urea buffer. Protein was then re-natured and purified with a GST chromatography column. The isolated protein was confirmed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blot using anti-GST antibodies, and its concentration was determined using the Bradford method. Each group of splenocytes was treated with 25 μg// ml of the recombinant protein (GST-RpfB), GST, and phytohemagglutinin. Antigen induction was repeated twice at 24 and 72 hours. The supernatant was collected at 96 hours and interferon gamma (IFNγ), interleukin (IL-12, IL-4, and IL-10) levels were measured with enzyme-linked immunosorbent assays. RESULTS GST-RpfB recombinant proteins were expressed in the form of inclusion bodies with a molecular weight of approximately 66 kDa. Based on the independent t-test, GST-RpfB stimulated IFNγ and IL-12 production but not IL-4 and IL-10. CONCLUSIONS The GST-RpfB protein has been immunogenically proven and is a potential candidate as a novel subunit TB vaccine.